2019
DOI: 10.1002/14651858.cd013308
|View full text |Cite
|
Sign up to set email alerts
|

Different doses, durations and modes of delivery of nicotine replacement therapy for smoking cessation

Abstract: Di erent doses, durations and modes of delivery of nicotine replacement therapy for smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
2
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(185 citation statements)
references
References 188 publications
6
141
2
18
Order By: Relevance
“…We advised participants to start using one patch per day, 2 weeks before their quit-date; although pre-cessation use of NRT is not mentioned as a treatment option in the New Zealand smoking cessation guidelines (unless as part of a cut-down to quit strategy), 19 trial evidence indicates this approach significantly increases long-term quitting success. 20 During this period, participants randomly assigned to an e-cigarette were advised to use the device as and when necessary or desired, and in accordance with the manufacturer's written instructions, to become familiar with its use. 3,21,22 In this way, the time-period of pre-cessation use of treatment products was matched.…”
Section: Methodsmentioning
confidence: 99%
“…We advised participants to start using one patch per day, 2 weeks before their quit-date; although pre-cessation use of NRT is not mentioned as a treatment option in the New Zealand smoking cessation guidelines (unless as part of a cut-down to quit strategy), 19 trial evidence indicates this approach significantly increases long-term quitting success. 20 During this period, participants randomly assigned to an e-cigarette were advised to use the device as and when necessary or desired, and in accordance with the manufacturer's written instructions, to become familiar with its use. 3,21,22 In this way, the time-period of pre-cessation use of treatment products was matched.…”
Section: Methodsmentioning
confidence: 99%
“…This may be due to the nicotine pre-loading (i.e. pre-quit NRT), which has been found to increase abstinence rates compared with not using NRT before quitting [7]. Nicotine patch pre-loading seems more effective than pre-loading with fast-acting NRT (e.g.…”
Section: Why Do Research Findings Differ?mentioning
confidence: 99%
“…Just over 17% of people who used a nicotine patch and another type of nicotine replacement therapy (NRT) such as gum or lozenges to stop smoking were successful, compared with about 14% who used only one type of NRT, a Cochrane review found 2. Higher dose nicotine gum (containing 4 mg nicotine) also worked better than lower doses.…”
Section: Lung Healthmentioning
confidence: 99%